Temperature distribution in multi-layer skin tissue in presence of a tumor. (December 2015) - Sarkar, Daipayan; Haji-Sheikh, A.; Jain, Ankur
Highlights: Bioheat transfer in a multilayer skin tissue is considered. Analytical solution for temperature field is derived. Effect of heat generation in a tumor during thermal-based cancer treatment is determined. Abstract: Analytical investigation of bioheat transfer is of significant importance for numerous medical applications, for example in thermally-driven treatments for cancer. While bioheat transfer has been investigated for a number of specific conditions, relatively less work exists on bioheat transfer in a multilayer structure, such as skin. This paper presents an analytical solution for the steady-state Pennes bioheat equation in a multi-layer structure. The temperature distribution in each layer is derived separately and interface temperature and heat flux compatibility conditions are used to determine the complete solution. This solution is used to analyze the effect of heat generation during thermal therapy on a tumor in skin, which is modeled as a five-layer structure. The model is capable of accounting for the effects of various therapeutic measures such as cryotherapy, laser treatment, etc. as well as various physical phenomena such as conduction, blood perfusion and metabolism. The model is used to analyze the effect of various physical parameters on the temperature distribution. This theoretical treatment, as well as the quantitative results presented here may help improve the fundamental understanding of bioheat transfer in a layered structure such as skin.